1983
DOI: 10.3406/revec.1983.4763
|View full text |Cite
|
Sign up to set email alerts
|

La prédation du Flamant rose Phoenicopterus ruber roseus par le Goéland leucophée Larus cachinnans en Camargue

Abstract: Yellow-legged herring gulls prey on the Greater Flamingo breeding colony in the Camargue, taking both eggs and chicks. They kill young chicks in their nest and flightless young forming large aggregates («crèches»). To rob nests the Yellow-legged herring gulls have developped a technique which forces the brooding flamingo to stand up. Once standing the brooding bird no longer defends its nest and the gull can take its content. Two or more gulls can cooperate when trying to catch larger chicks in a crèche.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…These findings are consistent with studies that found that disturbances generated by human and human activities increased the frequency of gull attacks and predation risk on several waterbird species (e.g. Salathé 1983, Åhlund & Götmark 1989, Keller 1991, Ludynia et al . 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with studies that found that disturbances generated by human and human activities increased the frequency of gull attacks and predation risk on several waterbird species (e.g. Salathé 1983, Åhlund & Götmark 1989, Keller 1991, Ludynia et al . 2014).…”
Section: Discussionsupporting
confidence: 92%
“…1998). They prey on the eggs and chicks of other waterbird species such as the Greater Flamingo Phoenicopterus ruber (Salathé 1983), Audouin's Gull Ichthyaetus audouinii (Oro & Martinez‐Vilalta 1994), Common Tern Sterna hirundo (Hernandez‐Matias & Ruiz 2003) and European Storm Petrel Hydrobates pelagicus (Oro et al . 2006).…”
mentioning
confidence: 99%